Intestinal Nematode Infection Ameliorates Experimental Colitis in Mice - Khan, W. I. (American Society for Microbiology, 2002)
Epidemiological studies suggest that inflammatory bowel disease (IBD) is common in developed countries and rare in countries where intestinal nematode infections are common. T cells are critical in many immune responses, including those associated with IBD and nematode infection. Among the distinct T helper (Th) cell subsets, Th1-type immune response is predominantly associated with Crohn's disease, while many nematode infections generate a strong Th2 response. The reciprocal cross regulation between Th1 and Th2 cells suggests that generation of a Th2 response by nematodes could prevent or reduce the effects of Th1-mediated diseases. In the present study, we investigated the effect of polarizing the immune response toward the Th2 type, using intestinal nematode infection, on subsequent experimental colitis. Mice were infected with the intestinal nematode Trichinella spiralis and allowed to recover before colitis was induced with dinitrobenzene sulfonic acid. The mice were sacrificed postcolitis to assess colonic damage macroscopically, histologically, and by myeloperoxidase (MPO) activity and Th cytokines. Prior nematode infection reduced the severity of colitis both macroscopically and histologically together with a decreased mortality and was correlated with a down-regulation of MPO activity, Th1-type cytokine expression in colonic tissue, and emergence of a Th2-type immune response. These results indicate a protective role of nematode infection in Th1 cell-driven inflammation and prompt consideration of a novel therapeutic strategy in IBD based on immunological distraction.